Fast Calculation of the Filamentary Coil Impedance Using the Truncated Region Eigenfunction Expansion Method - Grzegorz Tytko; Leszek Dziczkowski , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The paper presents a mathematical model of an ideal filamentary coil with a finite number of turns, derived by means of the method called truncated region eigenfunction expansion (TREE). The proposed solution allows quick computation of the filamentary coil impedance as well as of the impedance changes caused by the presence of a two-layered conductive material. The final formulas were presented in the closed form and implemented in Matlab. The results were verified using the finite element method in the COMSOL Multiphysics package as well as by means of other mathematical models. In all cases they show a very good agreement. The obtained values of coil impedance changes were compared in terms of the time of reaching the final results. In the case of the most significant calculations, which consisted of many iterations, the proposed solution turned out to be by far the fastest one.